Unsuspected faces: Borges, Brines, Valente - Marcela Romano (Universitat Autònoma de Barcelona, 2014)
My proposal focuses on linking some fifties spanish poets´creative projects (Brines and Valente, specifically) with Jorge Luis Borges. The bow is visibly established from the use, in all three cases, of a common enunciation key, the "dramatic monologue", whose formal enthronement begins with Browning and Tennyson in the last quarter of the nineteenth century. The convergence —in which the later Cernuda decisively takes part— lets guess, beyond the “influences”, common poetic programs, all alerted about the pathetic fallacy of certain Romanticism, and the commitment by a refined and meditative poetry.